Connarus favosus Planch.: An inhibitor of the hemorrhagic activity of Bothrops atrox venom and a potential antioxidant and antibacterial agent - Silva, Thaís Pereira da; Moura, Valéria Mourão de; Souza, Maria Carolina Scheffer de; Santos, Vanessa Neves Carvalho; Silva, Kiriaki Nurit M.Moreira da; Mendes, Mara Giselle Guimarães; Nunez, C. V.; Almeida, Patrícia Danielle Oliveira de; Lima, Emerson Silva; Mourão, Rosa Helena Veras; Santos, Maria Cristina dos (Journal of Ethnopharmacology, 2016)
Ethnopharmacological relevance The plant species Connarus favosus is used in folk medicine in the west of Pará state, Brazil, to treat snakebites. Aim of the study To investigate the potential of the aqueous extract of Connarus favosus (AECf) to inhibit hemorrhagic and phospholipase A2 activities induced by Bothrops atrox venom (BaV) and to determine the antioxidant and antimicrobial potentials of the extract. Materials and methods AECf was analyzed phytochemically for phenolics (condensed tannins and hydrolyzable tannins) by colorimetry. Antioxidant activity was evaluated by quantitative assays using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Fe3+/phenanthroline. Antimicrobial activity was evaluated by the minimal inhibitory concentration test, and cytotoxicity was evaluated using human fibroblast cells (MRC-5). Inhibition of BaV-induced hemorrhagic activity was assessed after oral administration of the extract using pre-treatment, post-treatment and combined (BA plus AECf) treatment protocols. Inhibition of indirect hemolysis caused by phospholipase A2 (PLA2) was investigated in vitro. Interaction between AECf and BaV was investigated by SDS-PAGE electrophoresis, Western blot (Wb) and zymography. Results The phytochemical profile of AECf revealed ten secondary metabolite classes, and colorimetry showed high total phenolic and total (condensed and hydrolyzable) tannin content. AECf exhibited high antioxidant and antimicrobial potentials. The IC50 for the cytotoxic effect was 51.91 (46.86-57.50) μg/mL. Inhibition of BaV-induced hemorrhagic activity was significant in all the protocols, and inhibition of PLA2 activity was significant with the two highest concentrations. The BaV/AECf mixture produced the same bands as BaV by itself in SDS-PAGE and Wb although the bands were much fainter. Zymography confirmed the proteolytic activity of BaV, but when the venom was pre-incubated with AECf this activity was blocked. Conclusion AECf was effective in reducing BaV-induced hemorrhagic activity when administered by the same route as that used in folk medicine and exhibited antioxidant and antimicrobial potentials. © 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: Antibiotic Agent; Antioxidant; Batroxobin; Connarus Favosus Extract; Phenanthroline; Phospholipase A2; Plant Extract; Tannin Derivative; Unclassified Drug; Antiinfective Agent; Antioxidant; Phospholipase A2; Plant Extract; Plant Medicinal Product; Snake Venom; Tannin Derivative; Venom Antiserum; Animals Experiment; Animals Model; Antibacterial Activity; Antioxidant Activity; Bleeding; Colorimetry; Controlled Study; Dpph Radical Scavenging Assay; Drug Cytotoxicity; Envenomation; Enzyme Activity; Female; Fibroblast; Hemolysis; Human; Human Cell; Ic 50; In Vitro Study; Male; Minimum Inhibitory Concentration; Mouse; Nonhuman; Phytochemistry; Electrophoresis, Polyacrylamide Gel; Protein Degradation; Quantitative Assay; Western Blotting; Zymography; Animals; Bothrops; Chemistry; Connaraceae; Hemorrhage; Metabolism; Procedures; Snake Bites; Medicine, Traditional; Animal; Anti-bacterial Agents; Antioxidants; Antivenins; Bothrops; Connaraceae; Crotalid Venoms; Female; Hemorrhage; Male; Medicine, Traditional; Mice; Phospholipases A2; Phytochemicals; Plant Extracts; Snake Bites; Tannins